Validity of water compartments estimated using bioimpedance spectroscopy in athletes differing in hydration status - Francisco, R.; Jesus, F.; Gomes, T.; Nunes, C. L.; Rocha, P.; Minderico, C. S.; Heymsfield, S. B.; Lukaski, H.; Sardinha, L. B.; Silva, A. M. (Scandinavian Journal of Medicine & Science in Sports, 2021)
We aimed to validate bioelectrical impedance spectroscopy (BIS), compared with tracer dilution measurements, for assessing total body water (TBW), intracellular water (ICW), and extracellular water (ECW) in athletes differing in hydration status. A total of 201 athletes participated. Reference TBW and ECW were determined by deuterium and bromide dilution methods, respectively; ICW was calculated as TBW-ECW. Water compartments were estimated by BIS. Urine specific gravity (USG) classified athletes into well-hydrated (WH) (USG < 1.023), euhydrated (EH) (USG:1.024-1.026), and dehydrated (DH) (USG>1.027). No significant differences were found between BIS and the reference methods for WH, EH, and DH athletes for TBW, ICW nor ECW (p>0.05). Concordance of TBW and its compartments by method was significant (p < 0.001) with coefficients of determination ranging by hydration classification [EH:52-96%;DH:56-98%;WH:71-96%]. Bland-Altman analyses showed no trend for TBW and its compartments with the exception of ICW in the WH athletes. The 95% confidence BIS intervals for the WH group ranged from -3.08 to 2.68 kg for TBW, -4.28 to 4.14 kg for ICW, and -3.29 to 3.02 kg for ECW. For the EH athletes, the 95% confidence intervals ranged from -2.78 to 2.24 kg for TBW, -4.10 to 3.94 kg for ICW, and -3.44 to 3.06 kg for ECW. In DH group, TBW ranged between -1.99 and 2.01 kg, ICW between -3.78 and 6.34 kg, and ECW between -6.22 and 3.74 kg. These findings show that BIS is useful at a group level in assessing water compartments in athletes differing in hydration status. However, the usefulness of BIS is limited at an individual level, especially in dehydrated athletes.